The impact of clinical teacher: the dental students’ perception / Nur Amni Noor Affendy ... [et al.] - Noor Affendy, Nur Amni; Mohd Zol, Syahirah; M. Abdullah Al -Jaf, Nagham; Abu Hassan, Mohamed Ibrahim; Abdul Ghani, Hazlina; Noviaranny, Indah Yuri (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
This study aims to evaluate the impact of the clinical teachers and the effectiveness of their supervisory skills in clinical settings from the dental students’ perception using the cognitive apprenticeship model. A total of 273 undergraduate clinical dental students, from Faculty of Dentistry UiTM, were asked to complete the modified and validated Maastricht Clinical Teaching Questionnaire (MCTQ) which consists of twenty-seven questions distributed on seven domains: Modelling, Coaching, Scaffolding, Articulation, Reflection, Exploration and General Learning Environment. The responses were descriptively analysed. Results: The cl inical experience of 162 dental students, who responded, was evaluated. Overall, the students conveyed positive and neutral perceptions of their clinical experience in all criteria of the seven domains. Articulation domain showed the highest positive feedback (93.5%) while the general learning environment domain showed the highest negative feedback (28.1%). The clinical experience and the impact of the clinical teachers were mostly satisfactory. Further improvements of the clinical environment can be achieved regarding the areas of concern